Use of Biosimilars in Pediatric Inflammatory Bowel Disease: An Updated Position Statement of the Pediatric IBD Porto Group of ESPGHAN. Issue 1 (January 2019) - de Ridder, Lissy; Assa, Amit; Bronsky, Jiri; Romano, Claudio; Russell, Richard K.; Afzal, Nadeem A.; Hauer, Almuthe C.; Knafelz, Daniela; Lionetti, Paolo; Strisciuglio, Caterina; Veres, Gábor; Winter, Harland; et al.
Abstract : ABSTRACT: Biologic therapies have changed the outcome of both adult and pediatric patients with Inflammatory Bowel Disease (IBD). In September 2013, the first biosimilar of infliximab was introduced into the pharmaceutical market. In 2015, a first position paper on the use of biosimilars in pediatric IBD was published by the ESPGHAN IBD Porto group. Since then, more data have accumulated for both adults and children demonstrating biosimilars are an effective and safe alternative to the originator. In this updated position statement, we summarize current evidence and provide joint consensus statements regarding the recommended practice of biosimilar use in children with IBD.